An ergonomic study of postural stress of nurses working in orthopedic wards - Goswami, Smaranika; Haldar, Prasun; Sahu, Subhashis (International Journal of Occupational Safety and Health, 2013)
It was reported high prevalence of musculoskeletal disorders among nurses. Among the wards, personnel working in Orthopedic wards routinely perform activities that require lifting heavy loads in awkward posture. Challenges faced by them assess patients skillfully and uniquely because orthopedic patients typically present with multiple, complex health problems. During orthopedic patient handling work-related postural strain are most common in health care unit personnel. This study aims at evaluating the different work-related musculoskeletal strain due to awkward postures, body parts discomforts, and find out some ergonomic solutions to these problems. Forty nurses working in orthopedic settings of two hospitals were interviewed by modified Nordic Questionnaire to reveal the prevalence of musculoskeletal problems and pain in various regions of the body. BPD Scale was used to identify the intensity of different body parts discomforts. Video recordings and still photographs were taken to evaluate postural stress during different activities were analyzed by OWAS (Ovako working posture analysis) method. Activity analysis chart was also used to represent the duration of different activities of nurses in their respective duty hours. It was observed that the most physically demanding and postural strenuous task is transferring patient alone. In orthopedics wards different activities like assist patient to walk, changing, other care works are strenuous because as about 90% of adult patient are over 50 kg of body weight and due to facture or other problem are unstable. Some ergonomic interventions like assisted lifting, lifting aids, training, etc. are recommended to improve the working conditions and reduce postural strain. DOI: http://dx.doi.org/10.3126/ijosh.v3i1.9097 International Journal of Occupational Safety and Health, Vol 3 No 1 (2013) 26-31